3D-Simulation of a Bayard Alpert ionisation gauge using SIMION program - Silva, Ricardo (2019)
This work has received funding from the EMPIR programme (project 16NRM05 'Ion gauge') co-financed by the Participating States and from the European Union's Horizon 2020 research and innovation programme. Authors would also like to express their gratitude for the financial support provided by FCT - Portuguese National Funding Agency for Science, Research and Technology, in the framework of the project UID/FIS/00068/2019.